Sequence homology between Moloney murine sarcoma virus and Moloney leukemia virus RNA. - Bondurant, M (1976)
The Moloney murine sarcoma-leukemia virus [M-MSV (MuLV)], propagated at high multiplicity of infection (MOI), was demonstrated previously to contain a native genome mass of 4 X 10(6) daltons as contrasted to a mass of 7 X 10(6) daltons for Moloney murine leukemia virus (M-MuLV). The 4 X 10(6)-dalton classof RNA from M-MSV (MuLV) was examined for base sequence homology with DNA complementary to the 7 X 10(6)-dalton M-MuLV RNA genome. Approximately 86% of the M-MSV (MuLV) was protected from RNase digestion by hybridization, whereas 95% of M-MuLV was protected under identical conditions. These results indicate that the small RNA class of high-MOI M-MSV (MuLV) contains little (perhaps 10%) genetic information not present in M-MuLV. Virtually all of the 1.8 X 10(6)-dalton subunits of M-MSV (MuLV) RNA contained regions of poly(A) since 94% of the RNA bound to oligo(dT) cellulose in 0.5 M KCl. This suggests that the formation of the 1.8 X 10(6)-dalton subunits occurs before their packaging into virions and does not result from hydrolysis of intact 3.5 X 10(6)-dalton subunits by a virion-associated nuclease.